ANALISIS KELAYAKAN PEMBANGUNAN TERMINAL KHUSUS (Studi Kasus: PT Union Perkasa Buana) - Rizky, Aldy Charlie; La Ode Alam Mindaris; Ma'ruf (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
PT Union Perkasa Buana (UPB) is a company that provides coal mining services that specifically provides coal transportation and sales services. In order to support its business activities PT UPB requires a port for its operational activities, but the nearest port cannot support its business activities so it requires the construction of a special terminal. Special Terminals are port facilities that are outside the Working Environment and Interests of the nearest port. This research aims to analyze the feasibility of PT Union Perkasa Buana's special terminal development plan. This research uses descriptive qualitative methods. The results of the analysis related to terminal facilities, depth, dock specifications, and ships that will dock / moor show that it does not interfere with the shipping channel and is feasible for operations in supporting the business activities of PT Union Perkasa Buana's Coal Transportation and Sales, with several aspects such as security and safety aspects of shipping port aspects